Emergence of Economic and Cultural Ties between USSR and Sweden (1924–1937) - O. V. Zaretskaya (Научный диалог, 2024)
This article explores the distinctive features of the economic and cultural interactions between the USSR and Sweden from 1924 to 1937. The research is grounded in a comprehensive array of sources, including official documents, publications from the periodical press, and personal accounts. The methodological framework is informed by the imagology of international relations, which focuses on the study of mental geography, transnational imagery, perception stereotypes, and myths, as well as the comparison of the "Self" and the "Other" to understand the role of "Others" in shaping national self-conceptions. The author investigates how shifts in Swedish perceptions of Soviet Russia influenced the development of bilateral relations and assesses the contributions of A.M. Kollontai, the Soviet ambassador to Sweden since 1930, to Soviet-Swedish interactions. The article illustrates how Swedish political figures, pursuing their own interests, viewed elements of Soviet society as potential models for reforming their own countries, shaped by their internal agendas of political and socio-economic change.